PENGARUH LKS BERBANTUAN SCAFFOLDING DALAM MODEL CREATIVE PROBLEM SOLVING (CPS) TERHADAP KREATIVITAS ILMIAH FISIKA SISWA SMA - Siti Iklimatul Fatimah; Sri Astutik; Supeno Supeno (JURNAL PEMBELAJARAN FISIKA, 2019)
Abstract Scaffold-assisted student worksheets in the creative problem solving model are provided in groups, while also facilitating student scientific creativity. The purpose of this study was to examine the variation of scaffold-assisted worksheets in the creative problem solving model of the scientific creativity of high school students. The type of research used is quasi-experimental. The method used is purposive sampling area. The sample in the study was in class X MIPA 3 and X MIPA 4. The research design used was Non Equivalent Control Group Design. The data in this study are the results of post-tests conducted at the end of the study. To see whether there was a variation of scaffold-assisted worksheets in the creative problem solving model of creativity using an independent sample t-test with the help of SPSS 23. Post-test average results are 60.21. Then tested using the independent sample t-test test, in which there was an influence between the scaffold assisted in the creative problem solving model of the scientific creativity of high school students. Key word: Scientific creativity, physics learning, student worksheets creative problem solving